Effect of Final Irrigation Materials and Techniques on Apical Sealing Ability of Bioceramic Sealer - Monika, Asteria; Ratih, Diatri Nari; Hadriyanto, Wignyo (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: One crucial function of root canal irrigation is eliminating smear layer, thus increasing apical sealing ability of endodontic sealers. This study was conducted to compare the effect of final irrigation using 17% EDTA, novel silver citrate, and 0.2% chitosan nanoparticles agitated manually, sonically, and ultrasonically on apical sealing ability of bioceramic sealers in the apical third.Method: Forty-five mandibular premolars were prepared and randomly divided into three experimental groups (n=15). Group 1 used 17% EDTA as the final irrigation, group 2 used novel silver citrate, and group 3 used 0.2% nanoparticle chitosan. Each group was divided into three subgroups (n=5), with subgroup A was using manual agitation, subgroup B using sonic, and subgroup C using ultrasonic. All teeth were obturated using single cone and bioceramic sealers. Observations were made using 120x magnification SEM. The sealer's apical sealing ability was measured by comparing cross-sectional area of obturation area with cross-sectional area of preparation area in the apical third.Result: Results of two-way ANOVA showed that there was a significant difference in final irrigation material (p<0.05), but there was no significant difference in technique and interaction of final irrigation material and technique (p>0.05).Conclusion: Irrigation materials affected the apical sealing ability of bioceramic sealers in the apical third, and 0.2% chitosan nanoparticles produced the highest apical sealing ability than other groups. There is no difference in effect of final irrigation technique and the interaction of materials and final irrigation technique on apical sealing ability of bioceramic sealers in the apical third.